2007
DOI: 10.1080/09513590701581721
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine regulation of endometriotic tissue

Abstract: Endometriosis is a chronic estrogen-dependent gynecological disease, characterized by pelvic pain and infertility, defined as the presence of endometrial glands and stroma within the pelvic peritoneum and other extrauterine sites. In the peritoneal cavity endometrial cells adhere, proliferate and induce an inflammatory response. Despite a long history of clinical and experimental research, the pathogenesis of endometriosis is still controversial. Abnormal immunological activation, the endocrine milieu and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 56 publications
1
17
0
1
Order By: Relevance
“…Klemmt et al (2006) has now suggested that in women with endometriosis the signalling cascade leading to decidualization might be impaired, potentially decreasing the biochemical maturation required for successful implantation. In addition, women with endometriosis display progesterone resistance (Burney et al, 2007) and their eutopic endometrium shows an impaired decidualization, a fact with important implications for uterine receptivity (Minici et al, 2007(Minici et al, , 2008. The decidualization is associated with an increase in endometrial expression of proteins involved in the suppression of immune cell activity.…”
Section: Altered Decidualizationmentioning
confidence: 97%
“…Klemmt et al (2006) has now suggested that in women with endometriosis the signalling cascade leading to decidualization might be impaired, potentially decreasing the biochemical maturation required for successful implantation. In addition, women with endometriosis display progesterone resistance (Burney et al, 2007) and their eutopic endometrium shows an impaired decidualization, a fact with important implications for uterine receptivity (Minici et al, 2007(Minici et al, , 2008. The decidualization is associated with an increase in endometrial expression of proteins involved in the suppression of immune cell activity.…”
Section: Altered Decidualizationmentioning
confidence: 97%
“…It is a major public health problem due to the morbidities associated with accompanying infertility and/or pelvic pain in affected women and an estimated cost for associated healthcare for diagnosis and treatment in 2002 totaling about $22B in the U.S. alone [1]. Infertility in women with endometriosis is believed to be related to the pro-inflammatory milieu in the pelvis affecting oocyte quality, fertilization, and embryo development, and impaired implantation due, in part, to compromised decidualization of endometrial stromal fibroblasts [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…-интерлейкина-1, -6, -11 (IL-I, -6, -11) [45,46]; -лейкемияингибирующего фактора (LIF) [47]; -сосудисто-эндотелиального фактора роста (VEGF) [48]; -гепаринсвязывающего эпидермального фак-тора роста (ГС-ЭФР) [49]; -матриксных металлопротеиназ (ММР) и их тканевых ингибиторов (ТIMP) [50]; -интегринов [46,47]; -селектинов [51,52]; -гликоделина A [53]; -кадгеринов [45]; -муцинов [45]; -простагландинов [54]; -белка Ki-67 [55,56]. Перечисленные молекулярные маркеры могут определяться в крови, секрете эндометрия или в са-мой ткани эндометрия, полученной при его биопсии.…”
Section: проблемы репродукции 5 2016unclassified